A Linguistically-Informed Assessment Model for Multidimensional Competence Building in Romanian School Writing - Alexandru Oravițan; Mădălina Chitez; Roxana Rogobete (Babes-Bolyai University, 2023)
In education, student involvement in writing activities is crucial for enhancing their learning experience and developing multiple competences. The development of any national curriculum within Europe is based on the indispensable competences required for lifelong learning as outlined in the European Parliament's Reference Framework. In response to the changing landscape of education, the Romanian national curriculum has undergone revisions that currently prioritise a competence-based approach to teaching writing. This approach aims to equip students with the necessary skills and knowledge to effectively communicate through writing, enabling them to express their ideas and thoughts clearly and concisely. Nevertheless, it is noteworthy that there has been a lack of research conducted to assess the efficacy of the didactic resources and materials developed to facilitate these educational goals. This study uses corpus linguistics methodologies to examine the correlation between the content of textbooks used for writing tasks in primary education, secondary education, and high schools and the pedagogical skills they aim to develop. For this purpose, we have constructed a preliminary textbook corpus called ROTEX, which consists of online materials, specifically Romanian language and communication textbooks approved by the Ministry of Education. The corpus includes three datasets, one for each educational level (4th grade, 8th grade, and 12th grade). Our analysis uses writing tasks to identify linguistic and thematic complexity patterns. This approach allows us to determine the competences that are effectively enhanced at each educational level. Our conclusions are backed up by quantitative linguistic evidence, which provides valuable insights into the dominant competences fostered within the educational framework.